Reliability and validity of the Indonesian version of the World Health Organization quality of life-old (WHOQOL-OLD): a Rasch modeling (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND The World Health Organization (WHO) has developed the WHOQOL-OLD instrument, specifically measuring the quality of life (QoL) of the elderly, but the Indonesian version of the WHOQOL-OLD has not been available. METHODS This study was conducted in 2 steps. First, the instrument was translated and pre-tested to 8 elderly respondents from 2 villages in Lembang, West Java, Indonesia. Second, Rasch modeling was used as implemented by the Winstep version 3.73 software to analyze the reliability, validity, value of separation, Wright map analysis, item-fit order, and differential item functioning in elderly respondents (aged ≥60 years old and did not have dementia) from 6 community health centers in Bangka Regency, Bangka Belitung, Indonesia from July to December 2018. RESULTS Overall, the Indonesian version of the WHOQOL-OLD demonstrated good reliability and validity tests in 175 respondents. The overall value of the person reliability was 0.73 with the Cronbach’s alpha of 0.75, and the value of the item reliability was 0.97. A misconception and bias occurred in the death and dying facet, especially in the demographic categories of age, gender, and marital status. CONCLUSIONS The Indonesian version of the WHOQOL-OLD module has good psychometric properties to measure the QoL of the Indonesian older population. However, further studies involving various ethnicities, religious groups, and districts in Indonesia should be carried out before the module can be used throughout the country.